Kurikulum Merdeka vs Kurikulum 2013: Tinjauan Perangkat Pembelajaran Matematika di MAN 1 Kota Padang - Adinda Azzahra Salsabila; Nita Putri Utami (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to evaluate learning planning based on the Merdeka Curriculum and the 2013 Curriculum at MAN 1 Padang City. The method used is descriptive qualitative through field observation and in-depth interviews with mathematics teachers and vice principals of madrasahs for curriculum. The research instruments are in the form of observation guidelines and interview guidelines. Data analysis techniques are carried out descriptively with the steps of data reduction, data presentation, and drawing conclusions. The results of the study show that teachers have compiled teaching tools such as RPP and teaching modules collaboratively and systematically. The assessment is carried out with a formative and summative approach and is accompanied by remedial and enrichment programs. The Olympiad program, use of books, LKPD, and teaching materials are also quite effective even though there are still obstacles such as limited time and variations in student abilities. In general, learning has led to a contextual and flexible approach. Thus it can be concluded that the Learning planning is very effective, namely 92,55%. Therefore, further training is needed to improve the quality of learning planning based on the Independent Curriculum.